2014
DOI: 10.1177/2167696814549598
|View full text |Cite
|
Sign up to set email alerts
|

Communicative Dilemmas in Emerging Adults’ Friends With Benefits Relationships

Abstract: Friends with benefits relationships (FWBRs) are a prevalent form of sexually intimate involvement among emerging adults, but research has only recently begun to develop a picture of how FWBRs are communicatively enacted. Research suggests that relational communication (i.e., communication about the nature of the relationship, expectations, and appropriate behavior) is necessary to successfully enact FWBRs but may be uncommon in practice. The current investigation employs qualitative analysis of interviews with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Life story interviews are often loosely structured by asking the participant to tell their life story as they see fit, allowing flexibility in how the participant accomplishes this (e.g., Schachter, 2004). Semi-structured interviews are more controlled, in that there are specific topics or themes that the interviewer aims to cover, but the order of those topics or themes and the specific wording or manifestation of those themes is determined in the interview setting and can vary from interview to interview (e.g., Knight, 2014). Semi-structured protocols are the most widely used in the social sciences because they offer the ability to cover the material the researcher is interested in, while at the same time allowing for the flexibility and openness that an interview affords (Weiss, 1994).…”
Section: Methods Of Data Collectionmentioning
confidence: 99%
“…Life story interviews are often loosely structured by asking the participant to tell their life story as they see fit, allowing flexibility in how the participant accomplishes this (e.g., Schachter, 2004). Semi-structured interviews are more controlled, in that there are specific topics or themes that the interviewer aims to cover, but the order of those topics or themes and the specific wording or manifestation of those themes is determined in the interview setting and can vary from interview to interview (e.g., Knight, 2014). Semi-structured protocols are the most widely used in the social sciences because they offer the ability to cover the material the researcher is interested in, while at the same time allowing for the flexibility and openness that an interview affords (Weiss, 1994).…”
Section: Methods Of Data Collectionmentioning
confidence: 99%
“…DTR talks may facilitate communication about commitment at these key moments, consistent with other research on commitment talk (Konstam et al, 2019). Importantly, having a DTR talk in a relationship does not presume any particular level of commitment; rather, DTR talks could be useful for defining relationships along the full continuum of commitment, from engagement and cohabitation (Rhoades et al, 2009; Stanley, Rhoades et al, 2010) to casual friends-with-benefits relationships (Bisson & Levine, 2009; Knight, 2014; Quirk et al, 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Uncertainty reduction theory (Berger & Calabrese, 1974) suggests uncertaintywhich can arise during turning points of relationship development, maintenance, and dissolution-can motivate interpersonal communication (e.g., Knobloch, 2010;Owen et al, 2014). At the same time, uncertainty makes vulnerable communication riskier and less likely, while less communication leads to continued uncertainty (Knight, 2014;Knobloch & Theiss, 2011;Knobloch & Carpenter-Theune, 2004). DTR talks could provide a needed framework for conversation about relationship definition and development, reducing uncertainty while also lowering the sense of risk involved in vulnerable communication.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, little is known about the role of communication within CSRs and how it relates to relational outcomes. Previous work (Bergdall et al, 2012; Knight, 2014) has suggested that individuals in CSRs may establish rules that intentionally limit or suppress communication. This has been suggested to serve as a relationship maintenance strategy, aimed at maintaining the relationship with its corresponding low level of commitment (Bisson & Levine, 2009; Knight, 2014).…”
mentioning
confidence: 99%
“…Previous work (Bergdall et al, 2012; Knight, 2014) has suggested that individuals in CSRs may establish rules that intentionally limit or suppress communication. This has been suggested to serve as a relationship maintenance strategy, aimed at maintaining the relationship with its corresponding low level of commitment (Bisson & Levine, 2009; Knight, 2014). While previous researchers have hypothesized about the relational outcomes associated with communication within CSRs, few have directly tested these assumptions.…”
mentioning
confidence: 99%